Contemporary design and digital fabrication - Tapia Abril, Verónica Emilia (Universidad de Cuenca, 2015)
From the introduction of CAD/CAM technologies in the 90’s, the paradigms of architecture were questioned and new ways to represent were included in architecture studies such is the case of Gehry and Associates, which was one of the first to implement digital processes for design. These events have allowed the introduction these technologies into teaching practices and give way to the creation of the first laboratories of digital fabrication, questioning the new role of the architect in the design and construction processes and give way to a world of possibilities through workshops that allow to explore different spatial and volumetric possibilities, as is the case of different laboratories created in a small number of universities.Keywords: Design, digital fabrication, architecture, University.